Quercetin Is a Novel Inhibitor of the Choline Kinase of Streptococcus pneumoniae - Tahl Zimmerman; Salam A. Ibrahim (MDPI AG, 2022)
The effectiveness of current antimicrobial methods for addressing for food-borne Gram-positive pathogens has dropped with the emergence of resistant strains. Consequently, new methods for addressing Gram-positive strains have to be developed continuously. This includes establishing novel targets for antimicrobial discovery efforts. Eukaryotic choline kinases have been highly developed as drug targets for the treatment of cancer, rheumatoid arthritis, malaria and many other conditions and diseases. Recently, choline kinase (ChoK) has been proposed as a drug target for Gram-positive species generally. The aim of this work was to discover novel, natural sources of inhibitors for bacterial ChoK from tea extracts. We report the first natural bacterial ChoK inhibitor with antimicrobial activity against Streptococcus pneumoniae: quercetin.